2000
DOI: 10.1063/1.1286329
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche multiplication in submicron AlxGa1−xAs/GaAs multilayer structures

Abstract: A systematic study of the role of band edge discontinuities on ionization rates in periodic AlxGa1−xAs/GaAs structures has been performed by measuring the electron and hole multiplication characteristics in a series of submicron AlxGa1−xAs/GaAs multilayer p–i–n and n–i–p structures. These structures comprise alternating 500Å AlxGa1−xAs and GaAs layers in the intrinsic multiplication regions, with a total thickness of up to 0.5 μm. The results show little dependence on initiating carrier type for multiplication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…4). Furthermore, as an approximation, we take the phonon scattering mean free path and the phonon energy from Chia et al [29] (for 45% Al concentration) as 4 nm and 32.5 meV, respectively. With these estimates at hand, we estimate the total phonon loss in the region in the vicinity of the GaAs i-layer as approximately 0.325 eV, which is approximately 17% of the initial energy when the mean gain is 20.…”
Section: B Excess Noise Factormentioning
confidence: 99%
See 1 more Smart Citation
“…4). Furthermore, as an approximation, we take the phonon scattering mean free path and the phonon energy from Chia et al [29] (for 45% Al concentration) as 4 nm and 32.5 meV, respectively. With these estimates at hand, we estimate the total phonon loss in the region in the vicinity of the GaAs i-layer as approximately 0.325 eV, which is approximately 17% of the initial energy when the mean gain is 20.…”
Section: B Excess Noise Factormentioning
confidence: 99%
“…In particular, we do not assume any localized change in the ionization coefficients as a result of bandedge discontinuity at the layer boundary beyond what is dictated by the type of material and the electric field. In fact, a recent Monte-Carlo study on Al Ga As/GaAs multilayers showed that bandedge discontinuities in multilayer structures offer no ionization-coefficient enhancement due to carrier energy losses brought about by phonon scattering [29].…”
mentioning
confidence: 99%
“…The method relies on the generation of random numbers to determine the occurrence of random events such as the termination of a carrier's free flight, selection of a scattering event, the change in flight angle and in momentum. A simple MC simulation program similar to that reported in the literature [3][4][5] has been used to study the hot carriers transport across the Ge-Al x Ga 1−x As heterojunction. Essential fitting parameters in the program such as phonon scattering and impact ionization rates, are obtained by fitting to the experimental data for bulk Ge ͑Refs.…”
mentioning
confidence: 99%
“…10,11 On the other hand, it was found that when the i-region thickness increases to above 300 nm, ␤ / ␣ reduces toward an average characteristic between the Ge and Al x Ga 1−x As because the effects of dead space becoming less significant when the device length becomes thicker. 22 Thin i-region is also expected to give lower noise due to a narrower ionization probability distribution, 23 the GaAs/ Al x Ga 1−x As APD with similar device dimension has been studied and reported in the literature 5,23,24 and has been shown to exhibit low excess noise. In the Ge/ Al x Ga 1−x As APD, the greater suppression of the ionization of opposite carrier as compared to the GaAs/ Al x Ga 1−x As structure could result in an even lower excess noise.…”
mentioning
confidence: 99%